Leigh syndrome: A rare mitochondrial disorder - Kundu, Gopen Kumar; Akhter, Amina; Akhter, Shaheen; Rhaman, Md. Mizanur (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Leigh syndrome is a rare, mitochondrial disorder of childhood . In most cases dysfunction of the respiratory chain enzymes is responsible for the disease. Raised lactate levels in blood and/or cerebrospinal fluid is noted. Magnetic resonance imaging showing characteristic symmetrical necrotic lesions in the basal ganglia and/or brain stem that leads to the appropriate diagnosis. Here, we report a case of progressive neurologic disorders presenting with motor and intellectual regression which on MRI was diagnosed as Leigh syndrome.